IMPLEMENTASI MODEL SIMULASI PADA PELATIHAN KEPALA MADRASAH - Mohammad Fauzan; Durahman Durahman (Balai Diklat Keagamaan Bandung, 2021)
This study aims to determine the effectiveness of simulation-based training model in terms of improving managerial competence among madrasah heads. The research was intended to the training participants on Substantive Technical Training to Strengthening Madrasah Heads since October 2019 - February 2020 with the cooperation of Bandung Religious Training Center, stakeholders and professional organization. Data collection techniques were conducted by tests (pre and post-test), questionnaire, observation, and structured interview. Data analysis is executed using qualitative approach. The results have shown that the training in the perspective of the process and results carried out effectively, with the average score 85 or competent. The aspect of training process resulted 89.9 or effective, and simulation-based training model application demonstrated score 90.2 which means also effective.Keywords: Simulation Model; Madrasah Head Training; Managerial Competence